2018
DOI: 10.1371/journal.pone.0200244
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of locomotor pointing across the lifespan: Investigating age-related influences on perceptual-motor coupling

Abstract: IntroductionThe regulation of one’s step length by placing one’s foot at a specific position within gait, otherwise known as ‘locomotor pointing’, is well understood in walking and running gait. The current study was the first to broaden this understanding to a larger cohort and to describe the influence of age on the regulation of locomotor pointing when walking up to and stepping onto a curb-like platform.MethodsYounger (n = 17, mean age: 25.35 years, range: 19–33) and older adults (n = 105, mean age: 71.49 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…For instance, when investigating locomotor pointing to step over an obstacle, Cornus et al (2009) showed that the strength of perceptual-motor coupling increased when both the walking speed and the obstacle size increased. These results illustrate that when individuals are confronted with higher task demands in a locomotor pointing task, they show stronger perceptual-motor coupling (Andel, Cole, & Pepping, 2018b).…”
mentioning
confidence: 63%
“…For instance, when investigating locomotor pointing to step over an obstacle, Cornus et al (2009) showed that the strength of perceptual-motor coupling increased when both the walking speed and the obstacle size increased. These results illustrate that when individuals are confronted with higher task demands in a locomotor pointing task, they show stronger perceptual-motor coupling (Andel, Cole, & Pepping, 2018b).…”
mentioning
confidence: 63%
“…One explanation for this may be found in a constraints-led interpretation of the coordination of walking [ 37 ]. In natural walking, performance is mainly dependent on individual constraints, such as preferred step length, and environmental constraints, such as a step or a stair that may be present on one’s planned route [ 38 , 39 ]. From this viewpoint, the metronome intervention might have resulted in increased task demands; instead of freely timing one’s steps, participants were asked to time this with the beats of the metronome.…”
Section: Discussionmentioning
confidence: 99%
“…As both orientation and action specification are required for successful control of movement, the enhancement of individual exploration strategies could have important implications for the practice environment. For instance, this could lead to interventions improving decision making on the sports field (McGuckian et al, 2019) or the perceptual guidance of gait in older adults (van Andel et al, 2018, 2019a).…”
Section: Discussionmentioning
confidence: 99%